The relationship between the SLC6A4 gene polymorphism (rs 5-HTTLPR) and aggression in combat athletes - Eda Bilen; Murat Elioz (Ozlem Book Center, 2023)
This study aimed to investigate the relationship between the SLC6A4 gene's 5-HTTLPR polymorphism and aggression levels among elite combat athletes. A total of 40 male athletes from taekwondo (N=10), kickboxing (N=10), boxing (N=10) and wrestling (N=10), aged between 20-35 years, participated in the study. The quantitative data was collected by using a personal information form and the Aggression Scale Inventory. Whole blood samples were taken for DNA isolation and genotyping analysis was performed. In 5-HTTLPR polymorphism, 38.8% (31) had the L allele and 61.3% (49) had the S allele. The highest S allele distribution in 5-HTTLPR polymorphism was found in taekwondo branch (32.7%). In 5-HTTLPR polymorphism, 77.5% (31) and 9% (22.5%) of the athletes had L/S and S/S genotyping, respectively. According to the aggression scale inventory, it was found that the wrestling branch had the highest general aggression mean (114.60), however; there was no significant difference between the sub-dimensions of aggression (Destructive, Attemptive and Passive) in branch comparisons (p>0.05). Based on the applied aggression scale inventory and genetic analysis of SLC6A4 gene 5-HTTLPR polymorphism, it can be considered that the combat athletes participating in the study are tend to aggression.